Postmarketing surveillance of enalapril. I: Results of prescription-event monitoring. - Inman, W. H. (1988)
To identify and measure the incidence of adverse effects of the angiotensin converting enzyme inhibitor enalapril 13,713 patients were studied for one year by prescription-event monitoring. Precise information about the duration of treatment was available for 12,543 patients. The frequency of many events was calculated, including dizziness (483 patients; 3.9%), persistent dry cough (360; 2.9%), headache (310; 2.5%) hypotension (218; 1.7%), and syncope (155; 1.2%). Less common reactions included angioedema, urticaria, and muscle cramps. Altogether 1098 (8%) patients died and the notes of 913 of them (83%) were obtained for detailed scrutiny. With the exception of a few patients with renal failure who deteriorated during treatment (reported on separately), no death was attributed to enalapril. Enalapril was considered to be effective, even in patients with advanced cardiac failure. These results for enalapril are reassuring and provide further evidence of the value of prescription-event monitoring.